046. Endoscopic Balloon Dilation for Releasing Post Operative Common Bile Duct Stricture: A-Case Report - Sona, Althof; Irwan, Irwan; Rivai, M. Iqbal; Suswita, Rini; Suchitra, Avit (JBN (Jurnal Bedah Nasional), 2024)
Background : CBD stones, or stones in the bile duct, affect approximately 10-15% of the global population, with 1-15% specifically experiencing bile duct stones. This prevalence is notably higher in Western populations, where around 20-25% may be affected. Case: We present a case of a 38-year-old woman who came to the polyclinic for a check-up after biliary stent installation 3 months ago. No jaundice was found, and postoperative pain was within normal limits. The patient had a history of LCBDE for indications of bile duct stones with the installation of a 10 Fr 9 cm biliary stent. Endoscopy confirmed the stent's position, after which it was extracted using a snare. A sphincterotomy facilitated the cannulation of the ampulla of Vateri. Cholangiography revealed dilation of both intra- and extrahepatic biliary tracts, with no gallstones detected but a stricture noted in the common bile duct (CBD). Sphincterotomy and balloon dilation were performed at the ampulla, followed by balloon dilation (CRE balloon at 3 atm, Ø 5 mm) at the stricture site. Post-procedure cholangiography indicated reduced stricture without contrast leakage, and the patient was stable for outpatient discharge the next day. Conclusion: Management of choledocholithiasis must be done properly. Several post-operative complications can occur, one of which is biliary stricture. In this case, dilation management with a dilation balloon has been performed. The stricture decreased after the procedure.